Cá tính ngôn ngữ trong nghiên cứu và giảng dạy ngoại ngữ - Lê, Đức Thụ (H. : ĐHQGHN, 2017)
The trend of linguistics and methodologies is changing from the study on the nature of language (systematic linguistics) into the experimental study (applied linguistics). Therefore, language users are supposed to be language preservers, representatives, users as well as reusers; they are of target-groups in all studies. Numerous Russian scientists including V.V. Vinogradov, N.Karaulov, Iu.E.Prokhorov studied on linguistic peculiarity in their latest science w orks.